A implementação da agenda de governo do presidente da república na democracia brasileira: uma análise da queda do governo Dilma - Barboza, Ingrid Eduardo Macedo (2021)
This paper analyzes the implementation of the government's agenda and the relationship between the president of the Republic and his parliamentary coalition, especially regarding the influence of these two elements for the maintenance of the government's mandate and for the stability of the presidential system. The study starts from an examination of the practical case of the fall of the Dilma Rousseff government, which, as a result of the association of factors such as popular dissatisfaction, loss of political support, accusations of corruption involving politicians related to her government, was removed from the presidential role as a result of impeachment process. The relevance of the research is demonstrated through the topicality of the subject. Since the events that culminated with the removal of the former president, much has been thought about the role of governors in the context of a representative democracy. The study adopts as its main theoretical frameworks the dimension of democracy as a process of popular participation, the principle of freedom to exercise the mandate and the Brazilian system as coalition presidentialism. Finally, the result is a proposal for the protagonism of political control of the citizen through electoral accountability, also called vertical accountability. The methodology used includes bibliographic and documentary research, especially works, scientific articles, theses and dissertations in the area of ​​law and political science, provisions of the Federal Constitution of 1988 and legislation, data extracted from official publications and the results presented by the institutes of research, in addition to journalistic articles and news disseminated in print, televised and digital media related to the period studied.